ANALYSIS OF BUSINESS STRATEGY IMPLEMENTATION AND CONSUMER BEHAVIOR IN PURCHASE AND ITS RELATIONSHIP TO COMPANY VALUE AT CV. HOMIE INDONESIA - Achmad Nauval Waliuddin (Jurnal Indonesia Sosial Sains, 2023)
This study seeks to comprehend the implementation of business strategy as well as the significance of studying consumer behavior in purchasing. Furthermore, the purpose of this research is to determine the relationship between business strategy implementation and consumer behavior in purchasing decisions and increasing a company's value. MSMEs play an important role in improving the national economy, lowering the unemployment rate, creating jobs, and becoming a resilient labor-intensive business sector in all circumstances. CV. Homie Indonesia is an Indonesian MSMEs with a competitive advantage, readiness for competitiveness, and the ability to adapt to changing times. This study employs a descriptive qualitative approach with a case study technique. The findings revealed that 1) CV. Homie Indonesia employs a variety of business strategies that are on point in the fields of service, production, marketing, and finance. 2) Cultural, social, personal, and psychological factors influence consumer behavior in purchasing decisions at CV. Homie Indonesia. 3) The study's findings also indicate a link or relevance between these two factors and an increase in the value or value of the company in CV. Homie Indonesia